Tugas Guru Mengembangkan Kecerdasan Anak Didiknya - Yazidul Busthomi (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2018)
Broadly speaking, the duties and responsibilities of a teacher is to develop the intelligence that exists within each of his students. This intelligence should be developed so that students can grow and grow into a smart human and ready to face any challenges in the future. Among the intelligences that need to be developed by a teacher are as follows; Intellectual intelligence, intellectual intelligence is an intelligence that seems to be excellent and developed with a larger portion in almost all formal schools in the world, including in Indonesia; Emotional intelligence, emotional intelligence is also developed in formal schools, but the portion is far below intellectual intelligence; Spiritual intelligence, in some studies in the field of intelligence and psychology, spiritual intelligence is said to be the most important intelligence. The three types of intelligence that exist in the students is very necessary to be noticed by a teacher so that the intelligence of children as a whole can be well developed. Broadly speaking, this is the duty and responsibility of a teacher in educating his students. A task and responsibility that is not light, but very important and noble, for the future generation of intelligent and noble character.